Поняття семантизації в сучасній лінгвістиці - Бук, С. (Видавництво Національного університету “Львівська політехніка”, 2004)
Статтю присвячено дослідженню лінгвістичного терміна ‘семантизація’. Описано специфіку його використання в романо-германській та східноєвропейській традиціях. Особливу увагу звернуто на вирішення проблеми його належності до лексикографії чи семасіології.

The linguistic term ‘semantization’ is investigated. The Romano-German and Eastern-European tradition of it functioning is described. The problem of its relation to either lexicography or semasiology is at the center of attention. Since the semasiology is the base of the lexicography, this term belongs at first to the semasiology and only the secondary meaning it developed in the lexicography.
Keywords: 81’37’373’374